Determinan Tingkat Pendapatan UMKM di Kecamatan Umbulharjo - G, Guntur; Rintasari, Nugraheni (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to examine the factors that influence the level of income of MSMEs in Umbulharjo District. The independent variables used are Business Location, Marketing Strategy, Business Capital, Education Level and the dependent variable is Income Level. This study is a quantitative study. The sample obtained was 52 respondents with a sample of MSMEs in Umbulharjo District. This study uses primary data which is a source of data obtained directly through a questionnaire. The analysis used is Multiple Linear Regression processed using SPSS25. The results of this study indicate that the variables of Business Location, marketing strategy, business capital, and education level partially have a significant effect on Sales Income. Keywords: Sales Income, Business Location, Marketing Strategy, Business Capital, Education Level and Multiple Linear Regression.